Physical and chemical analysis of two water courses for irrigation purposes in the city of Rio Verde – GO (Research, Society and Development, 2020)
Taking into account that Rio Verde is cut by several water courses, two were chosen: Ribeirão Abopard (1) and Córrego Barrinha (2). In this sense, the general objective of this study was to evaluate the water quality of these two treatments in order to meet the water needs of the crops according to the relationship proposed with Ayres and Westcot (1999), Richards (1954) and Resolution 357/05 CONAMA. The collections were carried out every 4 days, totaling a period of three months. The following characteristics were determined: pH, sodium absorption ratio (RAS), electrical conductivity, total dissolved solids (SDT) and turbidity. For the analyzes, the methodologies proposed by Almeida (2010) and APHA (2012) were used. The samples subsequently proceeded to statistical treatment, where a completely randomized design (DIC) was carried out in a 2 x 20 split plot scheme. The physical and chemical results showed normality within the proposed references even with oscillations from the rainy season.